Non‐Equilibrium Polymerization of Cross‐β Amyloid Peptides for Temporal Control of Electronic Properties. (26th May 2020) - Bal, Subhajit; Ghosh, Chandranath; Ghosh, Tapan; Vijayaraghavan, Ratheesh K.; Das, Dibyendu
Abstract: Hydrophobic collapse plays crucial roles in protein functions, from accessing the complex three‐dimensional structures of native enzymes to the dynamic polymerization of non‐equilibrium microtubules. However, hydrophobic collapse can also lead to the thermodynamically downhill aggregation of aberrant proteins, which has interestingly led to the development of a unique class of soft nanomaterials. There remain critical gaps in the understanding of the mechanisms of how hydrophobic collapse can regulate such aggregation. Demonstrated herein is a methodology for non‐equilibrium amyloid polymerization through mutations of the core sequence of Aβ peptides by a thermodynamically activated moiety. An out of equilibrium state is realized because of the negative feedback from the transiently formed cross‐β amyloid networks. Such non‐equilibrium amyloid nanostructures were utilized to access temporal control over its electronic properties. Abstract : The mutated core sequence of an Aβ peptide is shown to undergo non‐equilibrium polymerization driven by hydrophobic collapse. The paracrystalline packing of β‐sheets increases the proximity of the aromatic residues in the assembled state, contributing to temporal control over its electronic properties.